102k views
2 votes
3^x+2 + 3^x+1 = 4/3 solve​

User Buddah
by
5.4k points

1 Answer

12 votes


{3}^(x + 2) + 3 ^(x + 1) = (4)/(3) \\ = > {3}^(x) * {3}^(2) + {3}^(x) * 3 = (4)/(3) \\ = > {3}^(x) * 9 + {3}^(x) * 3 = (4)/(3) \\ = > {3}^(x) (9 + 3) = (4)/(3) \\ = > {3}^(x) * 12 = (4)/(3) \\ = > {3}^(x) = (4)/(3) * (1)/(12) \\ = > {3}^(x) = (1)/(3 * 3) \\ = > {3}^(x) = {3}^( - 2) \\ = > x = - 2

Answer:

x = -2

Hope you could understand.

If you have any query, feel free to ask.

User Ppreetikaa
by
5.2k points